2020
DOI: 10.1002/pi.5959
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene–nano‐silica nanocomposite foams: mechanisms underlying foamability, and foam microstructure, crystallinity and mechanical properties

Abstract: We investigate the production and characterization of foams prepared from polypropylene (PP) as well as PP–silica nanocomposites containing different loadings of nano‐silica. This study was carried out to investigate the mechanisms underlying the production of foams with a regular cell structure through the use of nano‐scale fillers. Foaming was carried out in batch mode using an autoclave with CO2 as the physical blowing agent; high pressures of the order of 14 MPa were achieved through a combination of activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…E. Laguna et al 12 observed that addition of small amount of silica nanoparticles (1 wt.%) in LDPE matrix reduces the cell sizes; however, with higher content of silica (3 and 6 wt.%), cell size was observed to increase and not show much variation. Similarly, A. Kumar et al 73 reported reduction in cell density of PP/silica nanocomposite foams with addition of silica nanoparticles and at higher content of silica (9 and 12 wt.%) there is slight increase in cell density. C. Saiz-Arroyo et al 15 reported decreasing nucleation density with increase in silica content in case of pressure quenched foaming; on the other hand, reverse trend was observed in case of chemical foaming for the same system.…”
Section: R1 R2mentioning
confidence: 77%
See 1 more Smart Citation
“…E. Laguna et al 12 observed that addition of small amount of silica nanoparticles (1 wt.%) in LDPE matrix reduces the cell sizes; however, with higher content of silica (3 and 6 wt.%), cell size was observed to increase and not show much variation. Similarly, A. Kumar et al 73 reported reduction in cell density of PP/silica nanocomposite foams with addition of silica nanoparticles and at higher content of silica (9 and 12 wt.%) there is slight increase in cell density. C. Saiz-Arroyo et al 15 reported decreasing nucleation density with increase in silica content in case of pressure quenched foaming; on the other hand, reverse trend was observed in case of chemical foaming for the same system.…”
Section: R1 R2mentioning
confidence: 77%
“…138 In this context, Chaudhary and Jayaraman 43 were able to correlate the observed improvements in the regularity of foam microstructure to the improved extensional strain hardening behaviour of the PP nanocomposite melts through incorporation of specially functionalized nano-clay that resulted in an intercalated microstructure. Similarly, in a study on PP -nanosilica nanocomposite foams, A. Kumar et al 73 concluded that the stability of foam growth seems to be enhanced through a synergistic effect of nano-silica on the melt elasticity and strain hardening at high orientations; the influence of nano-silica on enhancement of melt strength was found to be a more pronounced effect compared to its role as a heterogeneous nucleating agent. The enhancement of extensional viscosity with incorporation of nanofiller in semi-crystalline polymers, leading to improved cellular structure, has also been studied by other researchers 48,51,52,73,[139][140][141] -a few of these trends are captured in Figure 11.…”
Section: Nanocomposite Foams Processingmentioning
confidence: 91%
“…PVA-/silica-based fibres have also been incorporated with 3D printing to develop drug delivery patches [ 51 ]. Moreover, it has been demonstrated that the addition of nano-silica in PP resulted in the improvement of foam quality—as assessed from the well-defined and regular cell structures with absence of cell coalescence—as well as an increase in expansion ratio and decrease in foam density [ 52 ], and that significant improvements in the thermal stability were noticed with an increase in the percentage of nanosilica particles whereas the mechanical properties were improved [ 53 ], especially polypropylene modified by blending elastomer and nano-silica as the dispersed polyolefin elastomer could transfer and homogenize external mechanical forces [ 54 ], but for the electrical properties, when nano-SiO 2 was more dispersed in the PP phase, the space charge improvement effect was best [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because the molecular structure of PP is linear, the melt strength is very low, in addition, PP is also a semicrystalline material, which lead to poor foaming performance. [ 11,12 ] Especially at high temperature, the molten PP does not have enough viscosity to cover the gas produced in the foaming process. Some of the gases directly break out of the foams, or merge to form macroporous structure.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] A large number of studies have shown that the smaller the cell size is, the better the mechanical properties are. [ 11,23,24 ] The factors influencing cell size include melt strength, foaming duration and crystallization effect of materials, while the number and distribution of nucleation points in melt, external pressure and foam pressure in foaming process, gas production and foaming temperature will affect cell distribution, many factors need to meet an internal and external balance to get a good cell structure. [ 25,26 ] Therefore, simple control of single‐factor variables must not well meet the preparation requirements.…”
Section: Introductionmentioning
confidence: 99%